Role of increased mean platelet volume (MPV) and decreased MPV/platelet count ratio as poor prognostic factors in lung cancer. (6th January 2017) - Omar, Muhyettin; Tanriverdi, Ozgur; Cokmert, Suna; Oktay, Esin; Yersal, Ozlem; Pilancı, Kezban Nur; Menekse, Serkan; Kocar, Muharrem; Sen, Cenk Ahmet; Ordu, Cetin; Goksel, Gamze; Meydan, Nezih; et al.
Abstract: Objectives: In this study, they investigated whether mean thrombocyte volume (MPV) and MPV/platelet count ratio have a prognostic significance in advanced NSCLC or not. Methods: A total of 496 NSCLC patients at stage IIIB/IV and did not meet exclusion criteria were included in the study. The demographic features (age, gender, smoking habit), clinical characteristics (performance status, weight loss, disease stage, first‐line treatment regimen), laboratory tests (levels of hemoglobin, lactate dehydrogenase and calcium as well as MPV, MPV/platelet count ratio and counts of white blood cell, platelet), and histological features (histologic type, tumor grade) were recorded. Results: The MPV levels of all patients were determined as 10.2 {plus minus} 3.4 (range, 6.4‐14.1 fL). With ROC curve analysis, the MPV/PC ratio was associated with a sensitivity of 67.8% and a specificity of 84.8% at a cutoff value of 0.47424 for presence of brain metastasis at the time of diagnosis. Univariate analysis showed that OS was significantly shorter in the group with an increased MPV level than in the other group (median OS time 6.8 months vs. 11.5 months, log‐rank, P  = .032). Multivariate analysis confirmed that an increased MPV level was an independent poor prognostic factor for OS (HR: 1.704, 95% CI: 1.274‐3.415, P  = .014). Conclusions: Unlike results of previous studies, the study showed that increased MPV was an important prognostic factor in patients with NSCLC. Hence, an increased MPV level may be used as a prognostic biomarker to estimate for poor overall survival in patients with NSCLC.